(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This paper aims to reflect on the characterization of the character Ismael, in the play Anjo Negro, by Nelson Rodrigues. More specifically, the analysis seeks to demonstrate that Ismael, throughout the play, is constructed – by his words and actions, as well as by the information that the other characters present about him – as a “black angel”; image that evokes negative meanings, such as evil, cruelty and death. Such representation is constructed, mainly, in contrast to the image of Elias, a character who, in most acts, especially for the character Virgínia, reflects kindness, purity and delicacy, and whose physical appearance alludes to the figure of a common angel in the Christian imagination.